“On paper it was a surgical success, but the reality was very different”: A qualitative interview study using narrated casuistry to explore patient context in specialist care - Linda Modderkolk; Yvonne Schoon; Hugo Touw; Eva Stortelder; Marieke Voet; Yvonne Engels; Anne B. Wichmann (PLoS ONE, 2026)
Objective Approaches such as shared decision-making emphasize effective patient-provider communication to ensure that patient preferences are integrated into clinical practice. However, they often overlook crucial aspects of patient context, which can affect the appropriateness and feasibility of care planning. Applying a contextual care model addresses this gap, yet the extent to which relevant patient context is considered in routine clinical practice remains largely unknown. Previous studies have primarily focused on the United States, leaving a gap in understanding how care is contextualized in Europe. This study explored how medical specialists in the Netherlands interpret, perceive and incorporate patient context into care planning. Methods A qualitative interview study was performed with 18 medical specialists from 11 specialties working in academic and peripheral hospitals. Open coding was applied to explore how specialists defined and perceived patient context. Directed content analysis, based on the 4C coding process, was applied to analyze narrated case examples of contextualized and non-contextualized care. Results All participants acknowledged the importance of patient context for providing appropriate care, though they differed in how broadly they defined it – from physical and cognitive abilities, to social, emotional and environmental circumstances. Context was considered most relevant for making treatment decisions and, by half of the participants, for ongoing monitoring of treatment. Participants also described cases where contextualization developed over time or was shared among team members. Key challenges included distinguishing context from patient preferences and sufficiently probing red flags to inform care planning. Conclusion Medical specialists emphasized the essential role of patient context in enabling personalized and efficient decision-making, enhancing care monitoring, and ultimately improving clinical outcomes. However, systematic and continuous integration of contextual information into decision-making remains challenging. Addressing this requires proactive exploration, improved communication training, and organizational support to embed contextualized care in routine practice.